A Percepção dos professores de matemática sobre o uso pedagógico de objetos de aprendizagem na formação inicial e continuada - Oliveira, Gisele Pereira (2018)
Generally, the history of technology in education allows us to verify an advance in the use of digital information and communication technologies in the educational scenario, identifying the opportunity and necessity to hold discussions in the scope of Mathematics teacher training. One of the educational resources related to the technologies is the Objects of Learning (OA), that if elaborated and produced properly can provide the teaching and significant learning of mathematical concepts. Thus, the general objective is to know the perception of Mathematics teachers in the initial and continued training on the methodological use of Learning Objects. In order to reach this objective, our methodological procedure consisted of the elaboration of a university extension course with the theme of the pedagogical use of OAs as a didactic tool for the teaching of Mathematics. During this training we developed an educational product, in the form of a website, to host the materials produced and used, in order to contemplate the Second Generation Teaching Engineering. This research has a descriptive character, as we investigate the teachers' perception of Mathematics in relation to their teaching practices. In order to facilitate the descriptive research carried out in this study, we used the methodology of second generation didactic engineering, which assisted in the execution of the research stages, which were four: preliminary analysis, conceptions and a priori analysis of didactic engineering situations, experimentation and analysis a posteriori and validation. The analysis performed after the data collection was qualitative, with the help of the content analysis method of the extracted parts of texts raised during the experimentation phase, with the purpose of categorizing the teachers' perceptions in initial and continued formation, on the use of OAs as pedagogical tools for the teaching of Mathematics, having, finally, the accomplishment of the a posteriori analysis and validation of the research. Among the results obtained, we collected that 41% of the teachers participating in the course, sought to know innovative methodologies for teaching mathematics. And, through the data, we conclude that teachers in the initial and continuous period identify the pedagogical use of OAs as teaching tools that are helpful and facilitating the explanation, representation and experimentation of mathematical concepts.